Regional economic development in Lao PDR and Thailand : case studies of Savannakhet and Mukdaharn provinces during 1990-2006 - Tingthong Phetsavong (Chulalongkorn University, 2014)
Thesis (M.A.)--Chulalongkorn University, 2007